2020
DOI: 10.3390/ma13194223
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of ZnO Coatings Obtained by Atomic Layer Deposition (ALD) Method on a Cr-Ni-Mo Steel Substrate Type

Abstract: This paper aimed to investigate the structure and physicochemical and tribological properties of ZnO coatings deposited by ALD on 316L stainless steel for biomedical applications. To obtain ZnO films, diethylzinc (DEZ) and water were used as ALD precursors. Zinc oxide layers were deposited at the same temperature of 200 °C using three types of ALD cycles: 500, 1000 and 1500. The structure and morphology of ZnO coatings were examined using SEM and AFM microscopes. The XRD and GIXRD methods were used for the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The EIS test consists in determining the response of the tested electrical system at a determined free potential and current pulse [ 40 ]. An electrochemical examination was performed using the test stand comprised of an AutoLab’s PGSTAT 302N system (AutoLab, Warsaw, Poland), equipped with the frequency response analyzer (FRA2) module and an electrochemical cell with a three-electrode system, where the tested sample was used as a working electrode (anode), an auxiliary electrode was represented by a platinum wire (PtP-201), and the reference electrode was a saturated Ag/AgCl electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The EIS test consists in determining the response of the tested electrical system at a determined free potential and current pulse [ 40 ]. An electrochemical examination was performed using the test stand comprised of an AutoLab’s PGSTAT 302N system (AutoLab, Warsaw, Poland), equipped with the frequency response analyzer (FRA2) module and an electrochemical cell with a three-electrode system, where the tested sample was used as a working electrode (anode), an auxiliary electrode was represented by a platinum wire (PtP-201), and the reference electrode was a saturated Ag/AgCl electrode.…”
Section: Methodsmentioning
confidence: 99%
“…In order to compare different ALD thin films for their corrosion resistance, a 50 nm film is used as a model to accurately represent the corrosion properties of the ALD material. Staszuk et al [37] studied the electrochemical properties of ZnO films on Cr-Ni-Mo steel and found that it has improved the resistance to corrosion damage of the tested material, which was evidenced by the increasing values of the corrosion potential and polarization resistance. Staszuk et al [4] studied the effect of ZnO ALD layer on the adhesion of (Ti,Al)N Cathodic Arc Evaporation CAE-PVD coating on sialon substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Gara et al studied the friction and wear characteristics of ZnO water‐based nanofluids and found that the friction reduction effect is more obvious for smooth surfaces 21 . Furthermore, Zabinski et al 22 and Staszuk et al 23 provided coatings with low friction and long life by controlling the microstructure and chemical properties of ZnO. in addition, the surface wettability can be reversibly switched between hydrophobic and super hydrophilic states by controlling the number of oxygen vacancies in the ZnO surface layer 24 .…”
Section: Introductionmentioning
confidence: 99%